2003
DOI: 10.1046/j.0303-6987.2004.0131.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigen distribution and antigen‐presenting cells in skin biopsies of human chromoblastomycosis

Abstract: The data obtained suggest that chiefly macrophages, also Langerhans' cells and factor XIIIa+ dermal dendrocytes, function as antigen-presenting cells in chromoblastomycosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 15 publications
(22 reference statements)
3
34
1
5
Order By: Relevance
“…The localization of these cells, underlying the epidermis, perivascular areas and in the inflammatory cell infiltrate, is compatible with the role of antigen-presenting cells (APC). 16,[18][19][20] The examined lesions were from areas exposed to sunlight, and our findings are in contrast with the results of Hoyo et al 13 , who reported an increase in the number of these cells, as well as of several cytokines which are present in ACL, stimulated by the ultraviolet rays. Comparing the number of these cells in ACL with the number of cells in normal skin of the suprapubic region, that is unexposed to sunlight and in which the number of DD should be decreased, no statistically significant evidence was found.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…The localization of these cells, underlying the epidermis, perivascular areas and in the inflammatory cell infiltrate, is compatible with the role of antigen-presenting cells (APC). 16,[18][19][20] The examined lesions were from areas exposed to sunlight, and our findings are in contrast with the results of Hoyo et al 13 , who reported an increase in the number of these cells, as well as of several cytokines which are present in ACL, stimulated by the ultraviolet rays. Comparing the number of these cells in ACL with the number of cells in normal skin of the suprapubic region, that is unexposed to sunlight and in which the number of DD should be decreased, no statistically significant evidence was found.…”
contrasting
confidence: 56%
“…It is speculated whether the finding of a non-increased number of DDFXIIIa+, as in other research 16,19,20 , could result from the migration of LC/DD FXIIIa+ from skin to lymph nodes. A greater number of ACL cases and a comparison of the amount of DDFXIIIa+ with normal skin from sunexposed and unexposed areas are believed to be needed to achieve a statistically significant result.…”
mentioning
confidence: 98%
“…As citocinas como o TNF-α e a IL-1β, os receptores de quimiocinas, as moléculas de adesão e as metaloproteinases da matriz celular parecem estar envolvidos na capacidade migratória das CLs (Koch et al, 2006). Possivelmente, outros componentes responsáveis por desencadear a liberação de TNF-α pelos queratinócitos, parecem também atuar nesse processo de migração (Cumberbatch et al, 1999; (Cerio et al, 1989;Pagliari e Sotto, 2002;Sotto et al, 2004). Essas também se originam da família de monócitos/macrófagos, derivadas de células precursoras CD34+ da medula óssea.…”
Section: A Pele Como óRgão Imuneunclassified
“…É sabido que essas células além de sua capacidade de apresentação de antígeno, também têm competência fagocítica, tendo como base a presença de vacúolos no seu citoplasma contendo melanina e hemossiderina (Headington, 1986;Cerio et al, 1990;Nestle et al, 1998;Pagliari e Sotto;Sotto et al, 2004). A localização preferencial perivascular dos dendrócitos dérmicos FXIIIa+ na (Kadowaki, 2007).…”
Section: Não Encontramos Diferenças Na Quantificação Das Células Deunclassified
See 1 more Smart Citation